GWAS and RNA-seq reveal novel loci and genes of low-nitrogen tolerance in cucumber (Cucumis sativus L.) - Huaxiang Wu; Huiming Yan; Bowen Li; Yike Han; Yike Han; Nan Liu; Mengyu Fan; Yahan Liu; Mingjie Lyu; Shengli Du; Shengli Du; Shengli Du; et al. (Frontiers in Plant Science)
Cucumber (Cucumis sativus L.), a globally significant horticultural crop, requires substantial nitrogen inputs due to its high nutrient demand. However, the prevalent issues of low nitrogen use efficiency (NUE) in cultivars and excessive fertilizer application have led to increased production costs and environmental burdens. To identify quantitative trait nucleotides (QTNs) and genes associated with low-nitrogen tolerance, we conducted a genome-wide association study (GWAS) on a basis of three low-nitrogen tolerance traits and 594,066 single nucleotide polymorphisms (SNPs) of a natural population of 107 cucumber accessions. The transcriptome of low-nitrogen tolerant genotype (F005) and low-nitrogen sensitive genotype (F027) were sequenced between low and normal nitrogen treatments. Through GWAS, we identified 29 QTNs harboring 196 candidate genes, while RNA sequencing (RNA-seq) revealed 3,765 differentially expressed genes (DEGs). 24 were identified by both methods. Among these 24 genes, 20 genes showed significant phenotype differences among different haplotypes. These 20 genes were defined as more valuable candidate genes for low-nitrogen tolerance. Furthermore, functional validation of the candidate gene CsaV3_7G035390 (encoding a GATA9 transcription factor) was performed using virus-induced gene silencing (VIGS), which demonstrated that silencingn this gene significantly enhanced soil plant analysis development (SPAD) and leaf of nitrogen accumulation in cucumber, indicating its negative regulatory role in low-nitrogen tolerance. Collectively, this study provides novel genetic resources for improving NUE in cucumber breeding programs.